Negative electrode composition, negative electrode, lithium secondary battery, battery module, and battery pack

By adjusting the tap density of the negative active material so that the tap density of graphite is equal to or greater than that of the silicon-carbon composite, the problem of insufficient performance when designing lithium secondary batteries in a limited space is solved and fast charging performance is achieved , efficiency, service life and energy density improvement.

CN119366000APending Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380050484.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-11
Filing Date
2023-12-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Among lithium secondary batteries designed in limited spaces, the prior art is difficult to achieve optimal battery performance, especially in terms of fast charging performance, efficiency, service life and energy density.

Method used

By regulating the vibration density of negative active materials, the vibration density of graphite is equal to or more than the vibration density greater than silicon carbon complexes, thereby realizing the density density of graphite and constant adjustment of the orientation. Frequency frequency.

Benefits of technology

The rapid charging performance, efficiency, service life, and energy density of lithium secondary batteries designed in a limited space, avoiding the problem of increased electrode thickness and decreased capacity maintenance rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present invention relates to a negative electrode composition, a negative electrode, a lithium secondary battery, a battery module, and a battery pack, the negative electrode composition comprising a negative electrode active material, the negative electrode active material comprising a silicon-carbon composite and graphite, the graphite having a tap density equal to or greater than that of the silicon-carbon composite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention claims priority to and the benefit of Korean Patent Application No. 10-2022-0177137 filed on December 16, 2022, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0178444 filed on December 11, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.

[0002] The invention relates to a negative electrode composition, a negative electrode, a lithium secondary battery, a battery module and a battery pack. Background Art

[0003] Recently, with the rapid popularization of electronic devices (such as not only mobile phones, notebook-sized computers and electric vehicles, but also power tools and cleaners) using batteries, the demand for small and light secondary batteries with relatively high capacity and / or high output is increasing rapidly. In particular, lithium secondary batteries are lightweight and have high energy density, so they have attracted attention as driving power sources for electronic devices. Therefore, research and development efforts to improve the performance of lithium secondary batteries have been actively carried out.

[0004] Lithium secondary batteries generate electric energy through oxidation and reduction reactions during insertion and extraction of lithium ions at the positive and negative electrodes in a state in which an organic electrolyte or a polymer electrolyte is filled between positive and negative electrodes composed of an active material capable of inserting and extracting lithium ions.

[0005] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2, LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4), etc. have been used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its advantages of high operating voltage and excellent capacity characteristics, and is used as a high-voltage positive electrode active material. However, due to the rising price and unstable supply of cobalt (Co), its large-scale use as a power source in fields such as electric vehicles is limited, so there is a demand for the development of positive electrode active materials that can replace cobalt.

[0006] Therefore, a nickel-cobalt-manganese lithium composite transition metal compound (hereinafter referred to as "NCM lithium composite transition metal compound") has been developed, in which a portion of cobalt (Co) is replaced by nickel (Ni) and manganese (Mn). Recently, research has been conducted to increase the capacity of NCM lithium composite transition metal compounds by increasing the content of Ni in the compound. However, Ni-rich positive active materials with high nickel content have disadvantages such as increased resistance and increased gas generation due to deterioration of thermal stability and increase of side reactions during electrochemical reactions.

[0007] On the other hand, although graphite is commonly used as a negative electrode active material for lithium secondary batteries, it is difficult to increase the capacity of lithium secondary batteries due to the small unit mass capacity of 372 mAh / g of graphite. Therefore, in order to increase the capacity of lithium secondary batteries, negative electrode materials such as silicon, tin and their oxides have been developed as non-carbon-based negative electrode materials with higher energy density than graphite. However, although these non-carbon-based negative electrode materials have large capacity, these materials have the following problems: due to low initial efficiency, a large amount of lithium consumed during initial charge and discharge, and large irreversible capacity loss.

[0008] In addition, lithium secondary batteries have a required size according to their use, so it is necessary to design lithium secondary batteries in a limited space. Although consumers have an increasing demand for increasing energy density and improving high output performance, when using high-capacity positive electrode materials, there is no choice but to increase the content of negative electrode materials to meet the demand, thereby limiting the improvement of battery efficiency in a limited space. Therefore, it is necessary to develop batteries with improved performance (such as efficiency and service life) in a limited space.

[0009] <Related technical literature>

[0010] Korean Patent Application Publication No. 10-2011-0112215 Summary of the invention

[0011] Technical issues

[0012] The present inventors have found that, in a lithium secondary battery designed within a limited space, by adjusting the tap density of the negative electrode active material, optimal battery performance can be achieved in a negative electrode having a specific combination, thereby completing the present invention.

[0013] The invention relates to a negative electrode composition, a negative electrode, a lithium secondary battery, a battery module and a battery pack.

[0014] Technical Solution

[0015] An exemplary embodiment of the present invention provides a negative electrode composition including a negative electrode active material including a silicon-carbon composite and graphite, wherein a tap density of the graphite is equal to or greater than a tap density of the silicon-carbon composite.

[0016] An exemplary embodiment of the present invention provides a negative electrode including a negative electrode current collector; and a negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector and including the negative electrode composition according to the above exemplary embodiment.

[0017] An exemplary embodiment of the present invention provides a lithium secondary battery including: a positive electrode; the negative electrode according to the above exemplary embodiment; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0018] In exemplary embodiments, the positive electrode includes a lithium composite transition metal compound including nickel (Ni), cobalt (Co), and manganese (Mn) as a positive electrode active material, and the lithium composite transition metal compound may include a single particle.

[0019] An exemplary embodiment of the present invention provides a battery module including a lithium secondary battery.

[0020] An exemplary embodiment of the present invention provides a battery pack including a battery module.

[0021] Beneficial Effects

[0022] In the negative electrode composition according to an exemplary embodiment of the present invention, since the tap density of graphite in the negative electrode active material is equal to or greater than the tap density of the silicon-carbon composite, the graphite can be densely dispersed throughout the electrode, which makes the current flow in the negative electrode uninterrupted and makes it easy to adjust the orientation of the graphite in the negative electrode. Therefore, by adjusting the orientation of the graphite to a constant level, the ion transport channel in the electrode can be uniformly designed, and lithium (Li) diffusion occurs frequently, so that excellent performance can be exhibited during rapid charging of the battery.

[0023] In addition, by adjusting the orientation degree of graphite to a constant level, particle breakage during pressing can be prevented, which is beneficial to the dispersion of the electrode slurry, making rolling easier, reducing the thickness of the electrode, and increasing the mass per unit volume, thereby exhibiting denser properties.

[0024] Therefore, by using the negative electrode in which the tap density between the negative electrode active materials is adjusted as described above, the fast charging performance, efficiency, life span, and / or energy density of a lithium secondary battery designed within a limited space can be easily improved. DETAILED DESCRIPTION

[0025] Hereinafter, the present specification will be described in more detail.

[0026] In the present specification, when a part “comprises” one constituent element, unless otherwise specifically described, this does not mean excluding other constituent elements but means that other constituent elements may further be included.

[0027] In this specification, when “a member is arranged on another member”, this includes not only a case where one of the members is in contact with the other member but also a case where other members exist between the two members.

[0028] The terms or words used in the specification should not be construed as limited to the typical or dictionary meanings, and should be construed with meanings and concepts consistent with the technical gist of the present invention based on the principle that the inventor can appropriately define the concepts of the terms to describe his / her own invention in the best manner.

[0029] Singular expressions of the terms used in the present specification include plural expressions unless they have clearly contrary meanings in the context.

[0030] In this specification, "single particle" is a term used to distinguish particles from positive electrode active material particles in the form of secondary particles formed by aggregation of tens to hundreds of primary particles in the related art, and is intended to include a single particle composed of one primary particle and a quasi-single particle form that is an aggregate of 30 or less primary particles.

[0031] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve (graph curve of the particle size distribution graph). The average particle size can be measured using, for example, a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes from the submicron region to about several mm, and can obtain results with high reproducibility and high resolution.

[0032] The measurement of the average particle size can be confirmed using a Microtrac device (manufacturer: Microtrac, Inc., model name: S3500) using water and Triton-X100 dispersant. Specifically, the average particle size of the positive electrode active material can be measured in a refractive index range of 1.5 to 1.7, and the average particle size of the negative electrode active material can be measured under a refractive index condition of 1.97 or 2.42. For example, after the particles are dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device, the dispersion is irradiated with an ultrasonic wave of about 28 kHz at an output of 60 W, and then a volume cumulative particle size distribution diagram is obtained, and then the average particle size can be measured by obtaining a particle size corresponding to 50% of the volume cumulative amount.

[0033] Hereinafter, preferred exemplary embodiments of the present invention will be described in detail. However, the exemplary embodiments of the present invention may be modified into various other forms, and the scope of the present invention is not limited to the exemplary embodiments to be described below.

[0034] An exemplary embodiment of the present invention provides a negative electrode composition including a negative electrode active material including a silicon-carbon composite and graphite, wherein a tap density of the graphite is equal to or greater than a tap density of the silicon-carbon composite.

[0035] In an exemplary embodiment of the present invention, the negative electrode active material includes a silicon-carbon composite and graphite, and the tap density of the graphite may be equal to or greater than the tap density of the silicon-carbon composite.

[0036] Generally speaking, lithium secondary batteries have a required size according to their use and need to be designed in a limited space. Although consumers have an increasing demand for increased energy density and improved high output performance, when using high-capacity positive electrode materials, there is no choice but to increase the content of negative electrode materials to meet the demand, thereby limiting the improvement of battery efficiency in a limited space. In addition, depending on the type of the negative electrode material, it is necessary to design a positive electrode material with an efficiency that matches the efficiency of the negative electrode material.

[0037] Since the tap density of graphite in the negative electrode active material in the negative electrode composition according to the present invention is equal to or greater than the tap density of the silicon-carbon composite, graphite can be densely dispersed throughout the electrode, which makes the current flow in the negative electrode uninterrupted and makes it easy to adjust the orientation of graphite in the negative electrode. Therefore, by adjusting the orientation of graphite to a constant level, the ion transport channel in the electrode can be uniformly designed, and lithium (Li) diffusion occurs frequently, thereby being able to exhibit excellent performance during rapid charging of the battery.

[0038] In addition, by adjusting the orientation degree of graphite to a constant level, particle breakage during pressing can be prevented, which is beneficial to the dispersion of the electrode slurry, making rolling easier, reducing the thickness of the electrode, and increasing the mass per unit volume, thereby exhibiting denser properties.

[0039] Therefore, by using the negative electrode in which the tap density between the negative electrode active materials is adjusted as described above, the fast charging performance, efficiency, life span, and / or energy density of a lithium secondary battery designed within a limited space can be easily improved.

[0040] In contrast, when the tap density of graphite is less than the tap density of the silicon-carbon composite, the graphite aggregates in the electrode without dispersing, resulting in poor slurry dispersibility, which is not conducive to rolling, thereby increasing the thickness of the electrode and forming void areas in the electrode, which is not conducive to the uniformity of the electrode.

[0041] In the present specification, the silicon-carbon composite is a composite of Si and C, wherein Si and C (e.g., graphite) exist separately. For example, the respective peaks of Si and C can be observed by elemental analysis methods such as XRD or NMR. In the present specification, the silicon-carbon composite can be represented by Si / C. The silicon-carbon composite can be composed of Si and C that are not bound to each other, but can also contain other components if necessary. For example, the silicon-carbon composite may or may not contain silicon carbide represented by SiC. When the silicon-carbon composite contains silicon carbide, its content is 3% by weight or less. The silicon-carbon composite can exist in a crystalline, amorphous, or a mixture thereof. According to one example, C in the silicon-carbon composite can exist in an amorphous state. The carbon-silicon composite can be a physical or chemical composite of carbon and silicon materials, and is not limited as long as it is a composition in which carbon and silicon materials form a composite.

[0042] Specifically, the silicon-carbon composite can form a composition in which carbon is heat-treated (fired) in a state of being combined with silicon or silicon oxide particles to coat the surface of the particles with a carbon material, or a composition in which carbon is dispersed in a silicon particle in an atomic state, or a structure in which a core made of a composite of silicon, carbon, etc. is surrounded by graphite, graphene, amorphous carbon, etc.

[0043] According to an exemplary embodiment, the silicon-carbon composite includes porous carbon-based particles and silicon located on the surface or in internal pores of the porous carbon-based particles.

[0044] According to an exemplary embodiment, the silicon-carbon composite may be prepared by a method including forming silicon on the surface and in internal pores of porous carbon-based particles.

[0045] The porous carbon-based particles can be prepared using methods known in the art, and as an example, can be obtained by carbonizing an organic material (such as a petroleum-based material, a polymer, etc.) or chemically treating a natural material (such as coconut bark, etc.) and then carbonizing it. As another example, the porous carbon-based particles can be obtained by a method including etching a carbon-based particle containing internal pores to expand the internal pores of the carbon-based particle.

[0046] The expansion of the internal pores of the carbon-based particles can be performed in a nitrogen (N2) atmosphere, an oxygen (O2) atmosphere, or an air atmosphere. Specifically, the flow rate of oxygen (O2) or oxygen-containing air can be controlled at 0.1 to 10 L / min.

[0047] The expansion of the internal pores of the carbon-based particles may be performed at a temperature ranging from 400 to 1200° C. for 30 minutes to 4 hours.

[0048] Depending on the conditions for expanding the internal pores of the carbon-based particles, the pore characteristics of the obtained porous carbon-based particles may differ.

[0049] The formation of silicon may be performed using a chemical vapor deposition method. In this case, silicon nanoparticles may be deposited on the surface and / or in the internal pores of the carbon-based particles having expanded internal pores, thereby forming silicon in the form of a film, an island, or a mixture thereof.

[0050] The silicon nanoparticles may be crystalline, quasi-crystalline, amorphous, or a combination thereof.

[0051] In an exemplary embodiment of the present invention, the graphite may have a tap density of 0.9 g / cc to 1.2 g / cc, in particular, the tap density may be 1 g / cc to 1.2 g / cc, 1.03 g / cc to 1.15 g / cc, or 1.05 g / cc to 1.12 g / cc.

[0052] When the tap density of graphite satisfies the above range, graphite can be uniformly dispersed in the electrode without aggregation. In contrast, when the tap density of graphite is less than the above range, graphite may aggregate in the electrode without dispersion, or may form a void region in the electrode, which is disadvantageous in terms of electrode uniformity. When the tap density of graphite exceeds the above range, the graphite density in the electrode becomes too high, so that particle breakage may occur during rolling, which is disadvantageous in terms of lithium diffusion.

[0053] In an exemplary embodiment of the present invention, the silicon-carbon composite may have a tap density of 0.5 g / cc to 1.15 g / cc, in particular, 0.55 g / cc to 1.1 g / cc, or 0.58 g / cc to 1.08 g / cc.

[0054] When the tap density of the silicon-carbon composite satisfies the above range, the silicon-carbon composite can be uniformly dispersed in the electrode without aggregation. In contrast, when the tap density of the silicon-carbon composite is less than the above range, the silicon-carbon composite may aggregate in the electrode without dispersion, or may form a void region in the electrode, which is disadvantageous in terms of electrode uniformity. When the tap density of the silicon-carbon composite exceeds the above range, the density of the silicon-carbon composite in the electrode becomes too high, so that particle breakage may occur during rolling, which is disadvantageous in terms of lithium diffusion.

[0055] In an exemplary embodiment of the present invention, the tap density of the graphite may have the same value as the tap density of the silicon-carbon composite.

[0056] In an exemplary embodiment of the present invention, the tap density of the graphite may have a value greater than the tap density of the silicon-carbon composite.

[0057] In this specification, the tap density may be measured using a typical tap density measuring device, specifically, TAP-2S manufactured by LOGAN Co. For example, the tap density may be a density calculated by putting 40 g of a sample in a container and tapping the container 1000 times.

[0058] The graphite may be natural graphite or artificial graphite, or a mixture of natural graphite and artificial graphite.

[0059] When the graphite is a mixture of natural graphite and artificial graphite, a weight ratio of the natural graphite to the artificial graphite may be 50:50 to 90:10, specifically 60:40 to 80:20, or 65:35 to 75:25.

[0060] In an exemplary embodiment of the present invention, the silicon-carbon composite may have an average particle size (D 50 ). In addition, the silicon-carbon composite may have an average particle size of 15 μm or less. For example, the silicon-carbon composite may have an average particle size (D) of 1 μm or more and 15 μm or less, greater than 1 μm and less than 15 μm, 2 μm or more and 14 μm or less, 3 μm or more and 13 μm or less, 3 μm to 10 μm, 4 μm to 8 μm, or 5 μm to 8 μm. 50 ).

[0061] Even if the silicon-carbon composite is formed with a small particle size having an average particle size of 1 μm or more and 15 μm or less, the service life characteristics of the battery can be improved. For example, when the average particle size of the silicon-carbon composite is within the range of 1 μm or more and 15 μm or less, the volume expansion and contraction rate according to charge and discharge can be reduced, thereby improving the service life performance. In addition, the specific surface area is prevented from excessively increasing to prevent a side reaction with the electrolyte due to the progress of the cycle, thereby improving the service life performance.

[0062] In an exemplary embodiment of the present invention, the graphite may have an average particle size (D 50 ). Specifically, the average particle size may be 15 μm to 20 μm. When the average particle size of graphite satisfies the above range, the influence of particle aggregation is reduced and the slurry dispersibility can be improved.

[0063] According to an exemplary embodiment of the present invention, an average particle size of the silicon-carbon composite is smaller than an average particle size of the graphite.

[0064] According to an exemplary embodiment of the present invention, the graphite has an aspect ratio of 0.8 to 0.9, and the silicon-carbon composite has an aspect ratio of 0.3 to 0.7. When the aspect ratios of the graphite and the silicon-carbon composite are within the above range, there are advantages in production yield and calendering density. When the aspect ratio is equal to or lower than the upper limit, the yield of the material is excellent and the production cost is reduced, and when the aspect ratio is higher than or equal to the lower limit, the calendering density of the electrode is increased, so that particle depression and the like are less likely to occur.

[0065] According to an exemplary embodiment of the present invention, the graphite may have an aspect ratio of 0.8 to 0.90, or 0.83 to 0.90, and the silicon-carbon composite may have an aspect ratio of 0.3 to 0.7, or 0.42 to 0.70.

[0066] In the present specification, the aspect ratio may be a value obtained by dividing the circumference of a circle having the same area as the projected image by the circumference of the projected image when projecting the particle, and may be specifically represented by Formula 1. The aspect ratio may be obtained from a SEM image. An ion milling device may be used for cross-sectional analysis of the negative electrode active material. Specifically, an electrode sample prepared by coating a copper foil with a negative electrode active material is milled using a Hitachi IM4000 device. Specifically, the sample is irradiated with an ion beam at a voltage of 1.5 kV, each sample is treated for about 3 to 4 hours, and then a cross-sectional image may be measured using a Hitachi S4800 SEM. The aspect ratio of the negative electrode active material may be measured based on the measured SEM cross-sectional image.

[0067] [Formula 1]

[0068] Aspect ratio = circumference of a circle that has the same area as the projected image when the particle is projected / circumference of the projected image

[0069] According to an exemplary embodiment of the present invention, the graphite has a true density of 2 to 3 g / cc, and the silicon-carbon composite has a true density of 1.8 g / cc to 2.2 g / cc. When the true density of the graphite and the silicon-carbon composite is 2.2 g / cc or less, the graphite and the silicon-carbon composite are relatively easy to disperse in the slurry, thereby preventing the occurrence of positional deviation after the negative electrode active material layer is coated, and when the true density is 1.8 g / cc or more, phenomena such as particle scattering can be easily prevented, and the solid content of the slurry can be adjusted. According to an exemplary embodiment of the present invention, the graphite has a true density of 2 to 3 g / cc, 2 to 2.24 g / cc, or 2.23 to 2.24 g / cc, and the silicon-carbon composite may have a true density of 1.8 to 2.2 g / cc, or 1.9 to 2.2 g / cc.

[0070] The true density can be calculated by calculating the volume of the sample by the difference in volume before the sample is introduced into a container of known volume and after it is filled with He gas, and then dividing the weight of the sample by the volume.

[0071] According to an exemplary embodiment of the present invention, the graphite has a thickness of 1 to 3 m 2 / g, and the silicon-carbon composite has a BET specific surface area of ​​1 to 10 m 2 / g of BET specific surface area. In addition, the graphite may have a BET specific surface area of ​​1 to 3 m 2 / g, 1.0 to 2.2 m 2 / g, 1.0 to 2.1 m 2 / g, 1.7 to 3.0 m 2 / g, 1.7 to 2.2 m 2 / g, or 1.7 m 2 / g to 2.1 m 2 / g, and the silicon-carbon composite may have a BET specific area of ​​1 to 10 m 2 / g, 1.0 to 7.1 m 2 / g, 1.0 to 6.7 m 2 / g, 3.1 to 10 m 2 / g, 3.1 to 7.1 m 2 / g, or 3.1 to 6.7 m 2 / g BET specific surface area.

[0072] Generally, the lower the BET of the material, the easier it is to disperse the material in the slurry during mixing, which is conducive to increasing the density of the electrode. When the BET specific surface area of ​​the graphite and the silicon-carbon composite is within the above range, the acceleration of the side reactions during cycle life degradation and high temperature storage can be prevented by preventing the acceleration of the electrolyte side reactions. According to one example, the specific surface area is measured by the BET method, and can be specifically measured as follows: the measured object is degassed at 300 ° C for 1 hour using a BET measuring device (BEL-SORP-MAX, Bell Company, Japan), and N2 adsorption / desorption is performed at 77 K. That is, in this specification, the BET specific surface area means the specific surface area of ​​the particle itself measured by the measurement method.

[0073] According to an exemplary embodiment of the present invention, the negative electrode composition includes a silicon-carbon composite in an amount of 3 to 30 parts by weight based on 100 parts by weight of the total negative electrode active material. According to one example, the negative electrode composition may include a silicon-carbon composite in an amount of 3 to 20 parts by weight, or 3 to 13 parts by weight, preferably 5 to 10 parts by weight, based on 100 parts by weight of the negative electrode active material. By using the silicon-carbon composite within the above range, excellent battery characteristics can be exhibited when combined with the above-mentioned positive electrode material. In particular, when the content of the silicon-carbon composite is 3 parts by weight or more, the effect of using the silicon-carbon composite can be fully exhibited. In addition, since the silicon-carbon composite has a higher capacity than the SiOx-based active material, it may be difficult to balance the capacity with the positive electrode active material when used in excess. In particular, when the content of the silicon-carbon composite is 30 parts by weight or less, expansion during charge and discharge can be prevented, thereby improving cycle characteristics.

[0074] The silicon-carbon composite is a material having higher capacity and higher efficiency than silicon-based oxides, and can show excellent effects in terms of resistance compared to a negative electrode including silicon-based oxides and conductive materials even when no conductive material is included. In addition, since the silicon-carbon composite shows higher Si crystallinity than silicon-based oxides, excellent effects can be shown during high output evaluation.

[0075] In an exemplary embodiment of the present invention, the graphite may be natural graphite, artificial graphite or a mixture thereof. The content of the graphite may be 70 parts by weight or more and 97 parts by weight or less based on 100 parts by weight of the entire negative electrode active material contained in the negative electrode active material layer.

[0076] Based on 100 parts by weight of all the negative electrode active materials, the content of the graphite can be 75 parts by weight or more, 80 parts by weight or more, or 85 parts by weight or more. Based on 100 parts by weight of all the negative electrode active materials, the content of the graphite can be 95 parts by weight or less, 93 parts by weight or less, or 90 parts by weight or less. When the graphite is a mixture of artificial graphite and natural graphite, based on 100 parts by weight of the graphite, the artificial graphite and natural graphite can be included in a weight ratio of 90:10 parts by weight to 50:50 parts by weight, 85:15 parts by weight to 60:40 parts by weight, 80:20 parts by weight to 60:40 parts by weight, 80:20 parts by weight to 65:35 parts by weight, or 75:25 parts by weight to 65:35 parts by weight.

[0077] In an exemplary embodiment of the present invention, a weight ratio of the graphite to the silicon-carbon composite may be 0.1:99.9 to 30:70, 1:99 to 20:80, 5:95 to 20:80, 5:95 to 15:85, 8:92 to 12:88, or 10:90 to 12:88.

[0078] In an exemplary embodiment of the present invention, the content of the negative electrode active material in 100 parts by weight of the solid content of the negative electrode composition may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 97 parts by weight or more and 99.9 parts by weight or less.

[0079] In an exemplary embodiment of the present invention, the negative electrode composition may further include a negative electrode binder in addition to the silicon-carbon composite and graphite.

[0080] The negative electrode binder can be used to improve the bonding between the negative electrode active material particles and the adhesion between the negative electrode active material particles and the negative electrode current collector. As the negative electrode binder, those known in the art can be used, and its non-limiting example can include a group selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid and its hydrogen is replaced by Li, Na, Ca, etc. At least one of the group, and various copolymers thereof can also be included.

[0081] The content of the negative electrode binder may be 0.1 parts by weight to 50 parts by weight, for example, preferably 0.3 parts by weight to 35 parts by weight, more preferably 0.5 parts by weight to 10 parts by weight, based on 100 parts by weight of the solid content of the negative electrode composition.

[0082] The negative electrode composition may not contain a conductive material, but may contain a conductive material if necessary. The conductive material contained in the negative electrode composition is not particularly limited as long as the conductive material has conductivity and does not cause chemical changes to the battery. For example, graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; conductive materials, such as polyphenylene derivatives, etc. The content of the conductive material in the negative electrode active material may be 0.01 to 30 parts by weight, preferably 0.03 to 25 parts by weight, relative to 100 parts by weight of the negative electrode active material layer.

[0083] An exemplary embodiment of the present invention provides a negative electrode including a negative electrode current collector; and a negative electrode active material layer disposed on one or both surfaces of the negative electrode current collector and including the negative electrode composition according to the above exemplary embodiment.

[0084] According to an exemplary embodiment of the present invention, the negative electrode active material layer has a porosity of 23% to 28%, such as 24% to 27%, or 25% to 26%. When the porosity is equal to or lower than the upper limit of the above range, the energy density of the battery can be prevented from being reduced by preventing the reduction of the electrode density. When the porosity is equal to or higher than the lower limit of the above range, the particles of the active material in the electrode can be prevented from breaking. The porosity can be measured as follows. The porosity of the electrode active material layer can be determined from a value calculated from the true density of the material constituting the electrode active material layer and the weight, thickness, etc. of the active material. Specifically, the porosity is a value calculated by the following formula.

[0085] Porosity of electrode active material layer (%) = {1-(density of electrode active material layer / true density of electrode active material layer)} x 100

[0086] The true density of the electrode active material layer is obtained by pressing a 3*4 (cm 2 ) is pressed until the thickness of the negative electrode does not change, and the density of the electrode active material layer is the density of the electrode active material layer measured by sampling the electrode with the same size before pressing.

[0087] An exemplary embodiment of the present invention provides a lithium secondary battery including: a positive electrode; the negative electrode according to the above exemplary embodiment; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.

[0088] The positive electrode may include the positive electrode current collector and a positive electrode active material layer provided on one or both surfaces of the positive electrode current collector.

[0089] The positive electrode active material layer may have a porosity of 18% to 21%, such as 20% to 21%.

[0090] According to an exemplary embodiment, the positive electrode includes a lithium composite transition metal compound as a positive electrode active material, which includes nickel (Ni), cobalt (Co), and manganese (Mn).

[0091] In an exemplary embodiment of the present invention, the positive electrode active material includes nickel, cobalt, and manganese, and may further include aluminum.

[0092] In the present specification, the positive electrode active material contains 80 mol% or more, or 80 mol% or more and less than 100 mol% of nickel among metals other than lithium, and a lithium composite transition metal compound containing 80 mol% or more to less than 100 mol% of nickel among metals other than lithium may include one or more mixtures represented by the following Chemical Formula 1.

[0093] [Chemical Formula 1]

[0094] Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ

[0095] In the chemical formula, Q is any one or more elements selected from the group consisting of Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr, 1 ≤ a ≤ 1.5, 0 < b ≤ 0.5, 0 < c ≤ 0.5, 0 ≤ d ≤ 0.1, 0 < b + c + d ≤ 0.20, and -0.1 ≤ δ ≤ 1.0.

[0096] In the lithium composite transition metal compound of Chemical Formula 1, Li may be included in an amount corresponding to a, that is, 1 ≤ a ≤ 1.5. When a is less than 1, there is a concern that the capacity may decrease, and when a exceeds 1.5, there is a concern that the particles may be sintered during the firing process, making it difficult to prepare the positive electrode active material. Considering the balance between the effect of improving the capacity characteristics of the positive electrode active material by controlling the content of Li and the sinterability during the preparation of the active material, Li may be more preferably included in an amount of 1.1 ≤ a ≤ 1.2.

[0097] In the lithium composite transition metal compound of Chemical Formula 1, Ni can be included in an amount corresponding to 1-(b + c + d), for example, in an amount of 0.8 ≤ 1-(b + c + d) < 1. When the Ni content in the lithium composite transition metal compound of Chemical Formula 1 becomes a composition of 0.8 or more, a sufficient amount of Ni contributing to charge and discharge can be ensured to achieve high capacity. Preferably, 1-(b + c + d) as the Ni content can be 0.88 or more, preferably 0.9 or more, more preferably 0.93 or more. Preferably, 1-(b + c + d) as the Ni content can be 0.99 or less, or 0.95 or less.

[0098] In the lithium composite transition metal compound of Chemical Formula 1, Co can be included in an amount corresponding to b, that is, in an amount of 0 < b ≤ 0.5. When the Co content in the lithium composite transition metal compound of Chemical Formula 1 exceeds 0.5, there is a concern about an increase in cost. Considering the significant effect of improving capacity characteristics due to the inclusion of Co, Co can more specifically be included in an amount of 0.03 ≤ b ≤ 0.2.

[0099] In the lithium composite transition metal compound of Chemical Formula 1, Mn can be included in an amount corresponding to c, that is, in an amount of 0 < c ≤ 0.5. When c in the lithium composite transition metal compound of Chemical Formula 1 exceeds 0.5, there is a concern that the output characteristics and capacity characteristics of the battery may deteriorate instead, and Mn can more specifically be included in an amount of 0.01 ≤ c ≤ 0.2.

[0100] In the lithium composite transition metal compound of Chemical Formula 1, Q can be a doping element included in the crystal structure of the lithium composite transition metal compound, and Q can be included in an amount corresponding to d, that is, in an amount of 0 ≤ d ≤ 0.1. Q can be one or more selected from Na, K, Mg, Ca, Sr, Ni, Co, Ti, Al, Si, Sn, Mn, Cr, Fe, V, and Zr. For example, Q can be Al.

[0101] In an exemplary embodiment of the present invention, the lithium composite transition metal compound may include single particles.

[0102] In an exemplary embodiment of the present invention, the lithium composite transition metal compound may further include secondary particles.

[0103] The single particles can be prepared by mixing a transition metal precursor and a lithium raw material and firing the resulting mixture. The secondary particles can be prepared by a method different from that of the single particles, and the composition of the secondary particles can be the same as or different from that of the single particles.

[0104] For example, the firing is carried out at a temperature capable of forming a single particle. In order to form the single particle, it is necessary to fire at a higher temperature than when preparing the secondary particle. For example, when the composition of the precursor is the same, it is necessary to fire at a temperature of about 30°C to 100°C higher than when preparing the secondary particle. The firing temperature for forming the single particle may vary depending on the metal composition in the precursor. For example, when it is desired to form a high Ni NCM lithium composite transition metal oxide having a nickel (Ni) content of more than 80 mol % as a single particle, the firing temperature may be 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature satisfies the above range, a positive electrode active material containing a single particle with excellent electrochemical properties can be prepared. When the firing temperature is lower than 790°C, a positive electrode active material containing a lithium composite transition metal compound in the form of a secondary particle can be prepared, and when the firing temperature exceeds 950°C, over-firing may occur, so that a layered crystal structure may not be properly formed, thereby reducing the electrochemical performance.

[0105] In this specification, the single particle is a term used to distinguish a single particle from a secondary particle formed by the aggregation of tens to hundreds of primary particles in the related art, and is a concept including a single particle composed of one primary particle and a quasi-single particle that is an aggregate of 30 or less primary particles.

[0106] Specifically, in the present invention, the single particle may be in the form of a single particle composed of one primary particle, or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.

[0107] In an exemplary embodiment of the present invention, the tap density of the secondary particles may be greater than the tap density of the single particles.

[0108] In an exemplary embodiment of the present invention, the secondary particles may have a tap density of 2 g / cc to 3.2 g / cc. Specifically, the tap density may be 2.1 g / cc to 3 g / cc, or 2.2 g / cc to 2.9 g / cc, or 2.3 g / cc to 2.8 g / cc.

[0109] When the tap density of the secondary particles of the positive electrode active material satisfies the above range, the secondary particles of the positive electrode active material may be uniformly dispersed in the electrode without aggregation.

[0110] In an exemplary embodiment of the present invention, the single particle may have a tap density of 1.3 g / cc to 2.3 g / cc, in particular, the tap density may be 1.4 g / cc to 2.3 g / cc, 1.5 g / cc to 2.3 g / cc, or 1.6 g / cc to 2.25 g / cc.

[0111] When the tap density of a single particle of the positive electrode active material satisfies the above range, the single particle of the positive electrode active material may be uniformly dispersed in the electrode without aggregation.

[0112] In an exemplary embodiment of the present invention, the tap density of the single particle may be greater than the tap density of the graphite.

[0113] In an exemplary embodiment of the present invention, the single particles may have an average particle size (D 50 ). In addition, the single particle may have an average particle size of 12 μm or less. For example, the single particle may have an average particle size of about 1 μm or more and 12 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 6 μm or less, greater than 1 μm and 6 μm or less, 2 μm or more and 6 μm or less, or 3 μm or more and 5 μm or less.

[0114] Although the single particle is formed of a small particle size having an average particle size of 1 μm or more and 12 μm or less, the single particle can also have excellent particle strength, and the excellent particle strength can alleviate the phenomenon of an increase in the number of particles in the electrode due to particle breakage, thereby improving the service life characteristics of the battery. For example, when the single particle is subjected to 650 kgf / cm 2 When the single particle is pressed with a force of 650 kgf / cm 2 By strongly rolling the single particle, the phenomenon of increasing the number of particles in the electrode due to particle breakage can be alleviated, thereby improving the service life characteristics of the battery.

[0115] The method of forming the single particles is not particularly limited, but generally speaking, the single particles can be formed by increasing the firing temperature to achieve overfiring, and the single particles can be prepared by using additives (such as grain growth promoters that assist overfiring) or changing the starting material method.

[0116] The single particle itself has high rigidity and is therefore relatively excellent in preventing battery performance from deteriorating even when the electrode density is high. Therefore, the energy density can be increased by adjusting the average particle size range of the single particle and the silicon-carbon composite.

[0117] In an exemplary embodiment of the present invention, the average particle size of the single particles may be smaller than the average particle size of the silicon-carbon composite.

[0118] When the average particle size of the single particles is smaller than the average particle size of the silicon-carbon composite, the diffusion resistance of the single particles can be relatively reduced, thereby improving the service life performance. That is, as the average particle size of the single particles increases, the diffusion resistance may increase, and when the average particle size of the single particles is larger than the average particle size of the silicon-carbon composite, lithium precipitation may occur due to the relative increase in diffusion resistance, thereby causing degradation of battery performance and degradation of service life performance.

[0119] In addition, when the average particle size of the single particles is smaller than the average particle size of the silicon-carbon composite, a side reaction with an electrolyte due to an increase in specific surface area can be prevented, thereby improving service life performance.

[0120] According to an exemplary embodiment of the present invention, the average particle size of the single particle may be 1 μm to 12 μm smaller than the average particle size of the silicon-carbon composite. Specifically, the average particle size of the single particle may be 1.5 μm to 11.5 μm, or 2 μm to 11 μm smaller than the average particle size of the silicon-carbon composite.

[0121] When the average particle size of the single particles is smaller than the average particle size of the silicon-carbon composite, for example, when the above range is satisfied, the diffusion resistance of the single particles can be relatively reduced, thereby improving the service life performance. That is, as the average particle size of the single particles increases, the diffusion resistance may increase, and when the average particle size of the single particles is larger than the average particle size of the silicon-carbon composite, lithium precipitation may occur due to the relative increase in diffusion resistance, thereby causing degradation of battery performance and degradation of service life performance.

[0122] Furthermore, when the average particle size of the single particles is smaller than that of the silicon-carbon composite, for example, when the above range is satisfied, a side reaction with an electrolyte due to an increase in specific surface area can be prevented, thereby improving life performance.

[0123] According to an exemplary embodiment of the present invention, a ratio of an average particle size of the single particles to an average particle size of the silicon-carbon composite may be 1.5:2 to 1.5:20.

[0124] When the above range is met, the diffusion resistance of the single particle can be relatively reduced to improve the service life performance. That is, as the average particle size of the single particle increases, the diffusion resistance may increase. When the average particle size of the single particle is larger than the average particle size of the silicon-carbon composite, lithium precipitation may occur due to the relative increase in diffusion resistance, thereby causing degradation of battery performance and service life performance.

[0125] Furthermore, when the average particle size of the single particles is smaller than that of the silicon-carbon composite, for example, when the above range is satisfied, a side reaction with an electrolyte due to an increase in specific surface area can be prevented, thereby improving life performance.

[0126] In an exemplary embodiment of the present invention, the lithium composite transition metal compound further includes secondary particles, and an average particle size of the single particles is smaller than an average particle size of the secondary particles.

[0127] In the present invention, the single particle may be in the form of a single particle composed of one primary particle, or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.

[0128] The lithium composite transition metal compound may further include secondary particles. The secondary particles are formed by aggregation of primary particles and can be distinguished from the concept of single particles including one primary particle, one single particle, or a quasi-single particle that is an aggregation of 30 or less primary particles.

[0129] The secondary particles may have an average particle size (D50) of 1 to 20 μm. Specifically, the secondary particles may have an average particle size of 2 to 17 μm, 3 to 15 μm, 5 to 15 μm, 7 to 15 μm, or 9 to 15 μm.

[0130] The secondary particles may have a size of 0.05 μm 2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3 m 2 / g to 0.8 m 2 / g specific surface area (BET).

[0131] In an exemplary embodiment of the present invention, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size of 0.5 μm to 3 μm. Specifically, the secondary particles may be aggregated in the form of hundreds of primary particles, and the primary particles may have an average particle size of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.

[0132] When the average particle size of the primary particles satisfies the above range, a single-particle positive electrode active material with excellent electrochemical properties can be formed. When the average particle size of the primary particles is too small, the number of aggregated primary particles forming lithium nickel oxide particles increases, thereby reducing the effect of suppressing particle breakage during rolling, and when the average particle size of the primary particles is too large, the lithium diffusion path inside the primary particles becomes longer, thereby increasing resistance and possibly deteriorating output characteristics.

[0133] In an exemplary embodiment of the present invention, the average particle size of the single particle may be smaller than the average particle size of the secondary particle. Therefore, even if the single particle is formed into a small particle size, the single particle may have excellent particle strength, and the excellent particle strength may reduce the phenomenon of an increase in the number of particles in the electrode due to particle breakage, thereby improving the service life characteristics of the battery.

[0134] In an exemplary embodiment of the present invention, the average particle size of the single particles is 1 μm to 18 μm smaller than the average particle size of the secondary particles.

[0135] For example, the average particle size of the single particles may be smaller than the average particle size of the secondary particles by 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm.

[0136] When the average particle size of the single particle is smaller than the average particle size of the secondary particle, for example, when the above-mentioned range is met, the single particle can have excellent particle strength even if it is formed with a small particle size. Therefore, the excellent particle strength alleviates the phenomenon of increased number of particles in the electrode due to particle breakage, thereby having the effect of improving the service life characteristics of the battery and improving the energy density.

[0137] In an exemplary embodiment of the present invention, the average particle size of the silicon-carbon composite may be smaller than the average particle size of the graphite. When the average particle size of the silicon-carbon composite is smaller than the average particle size of the graphite, the volume expansion / contraction rate during charge and discharge is reduced, and particle breakage is reduced, thereby having the effect of improving the service life performance of the battery.

[0138] In the lithium secondary battery according to the exemplary embodiment described above, the negative electrode active material may further include a carbon-based active material. Specifically, the carbon-based active material may be graphite. The graphite may be natural graphite, artificial graphite, or a mixture thereof.

[0139] According to an exemplary embodiment of the present invention, the average particle size of the silicon-carbon composite may be 1 μm to 25 μm smaller than the average particle size of the graphite. For example, the average particle size of the silicon-carbon composite may be 2 μm to 24 μm smaller than the average particle size of the graphite, 3 μm to 23 μm smaller, or 4 μm to 22 μm smaller.

[0140] When the average particle size of the silicon-carbon composite is smaller than the average particle size of the graphite, for example, when the above range is satisfied, there is an effect of further improving the service life performance of the battery.

[0141] In an exemplary embodiment of the present invention, when the average particle sizes of the secondary particles, the single particles, the graphite, and the silicon-carbon composite included in the lithium secondary battery are A, B, C, and D, respectively, A, B, C, and D may satisfy the relationship of B < D ≤ A < C.

[0142] Exemplary embodiments of the secondary particles, the single particles, the graphite, and the silicon-carbon composite are as described above.

[0143] When the average particle sizes of the secondary particles, the single particles, the graphite, and the silicon-carbon composite are A, B, C, and D, respectively, the case of B < D ≤ A < C has an effect of improving the service life performance of the battery.

[0144] According to an exemplary embodiment of the present invention, the negative electrode active material further includes graphite, and when the average particle sizes of the single particles, the graphite, and the silicon-carbon composite (D 50 ) are B, C, and D, respectively, B, C, and D may satisfy the relationship of B < D < C.

[0145] When the average particle sizes of the secondary particles, the single particles, and the silicon-carbon composite are A, B, and D, respectively, A, B, and D may satisfy the relationship of B < D ≤ A.

[0146] When the average particle sizes of the secondary particles, the single particles, and the graphite are A, B, and C, respectively, A, B, and C may satisfy the relationship of B < A < C.

[0147] When the average particle sizes of the secondary particles, the graphite, and the silicon-carbon composite are A, C, and D, respectively, A, C, and D may satisfy the relationship of D ≤ A < C.

[0148] When the above range is satisfied, there is an effect of improving the service life performance of the battery.

[0149] In an exemplary embodiment of the present invention, in the lithium secondary battery according to the above exemplary embodiment, the content of the single particle is 15 to 100 parts by weight relative to 100 parts by weight of the positive electrode active material, and the content of the silicon-carbon composite is 3 to 30 parts by weight relative to 100 parts by weight of the negative electrode active material.

[0150] In an exemplary embodiment of the present invention, the content of the single particle is 15 to 100 parts by weight relative to 100 parts by weight of the positive electrode active material. The content of the single particle may be 20 to 100 parts by weight, or 30 to 100 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0151] For example, relative to 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. For example, relative to 100 parts by weight of the positive electrode active material, the content of the single particle may be less than 100 parts by weight, less than 90 parts by weight, less than 80 parts by weight, less than 70 parts by weight, or less than 60 parts by weight.

[0152] When the single particle is included within the above range, excellent battery characteristics can be exhibited when combined with the above negative electrode material. In particular, when the amount of the single particle is 15 parts by weight or more, the phenomenon of an increase in the number of particles in the electrode due to particle breakage during the rolling process after manufacturing the electrode can be alleviated, thereby improving the service life characteristics of the battery.

[0153] In an exemplary embodiment of the present invention, the lithium composite transition metal compound may further include the secondary particles, and the amount of the secondary particles may be 85 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The amount of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, 70 parts by weight or less, or 60 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The amount of the secondary particles may be 10 parts by weight or more, 20 parts by weight or more, 30 parts by weight or more, or 40 parts by weight or more relative to 100 parts by weight of the positive electrode active material.

[0154] In an exemplary embodiment of the present invention, a weight ratio of the single particle to the secondary particle may be 1:9 to 9:1, 2:8 to 8:2, 3:7 to 7:3, or 4:6 to 6:4.

[0155] When the above range is met, the above effect due to the presence of the single-particle positive electrode active material can be maximized. When the secondary particle positive electrode active material is included, the composition may be the same as the composition exemplified as the single-particle positive electrode active material, or may be a different composition, and may refer to a form of aggregation in a single particle form.

[0156] In an exemplary embodiment of the present invention, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.

[0157] According to an exemplary embodiment of the present invention, the positive electrode active material layer further includes the positive electrode binder and a conductive material.

[0158] The positive electrode binder can be used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material particles and the positive electrode current collector. As the positive electrode binder, those known in the art can be used, and non-limiting examples thereof include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof can be used.

[0159] The content of the positive electrode binder may be 0.1 parts by weight or more and 50 parts by weight or less, for example, preferably 0.3 parts by weight or more and 35 parts by weight or less, more preferably 0.5 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the positive electrode active material layer.

[0160] The conductive material contained in the positive electrode active material layer is used to impart conductivity to the electrode, and can be used without particular limitation as long as the conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples thereof include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of them or a mixture of two or more of them can be used.

[0161] Specifically, in an exemplary embodiment, the conductive material may include one or more of single-walled carbon nanotubes (SWCNTs); and multi-walled carbon nanotubes (MWCNTs). Based on 100 parts by weight of the positive electrode active material layer composition, the content of the conductive material may be 0.1 parts by weight or more and 2 parts by weight or less, for example, preferably 0.3 parts by weight or more and 1.5 parts by weight or less, more preferably 0.5 parts by weight or more and 1.2 parts by weight or less.

[0162] The positive electrode current collector is not particularly limited as long as the current collector has conductivity without causing chemical changes to the battery, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can generally have a thickness of 1 to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine concavoconvexities on the surface of the current collector. For example, the positive electrode current collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0163] The negative electrode current collector is not particularly limited as long as it has conductivity without causing chemical changes to the battery. For example, as the current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, etc. can be used. Specifically, transition metals such as copper or nickel that adsorb carbon well can be used as current collectors. Although the current collector may have a thickness of 1 μm to 500 μm, the thickness of the current collector is not limited thereto.

[0164] In an exemplary embodiment of the present invention, the positive electrode active material layer and the negative electrode active material layer each have a thickness of 10 μm or more and 500 μm or less. The thickness of the positive electrode active material layer may be 90% to 110% of the thickness of the negative electrode active material layer, for example, 95% to 105%, and the thickness of the active material layers may be the same. Specifically, the positive electrode active material layer and the negative electrode active material layer may each have a thickness of 15 μm or more and 400 μm or less, 20 μm or more and 300 μm or less, 25 μm or more and 200 μm or less, or 30 μm or more and 100 μm or less.

[0165] In an exemplary embodiment of the present invention, the loading amount per unit volume of the positive electrode active material layer is 250 mg / 25 cm 2 Up to 900 mg / 25 cm 2 , and the loading amount per unit volume of the negative electrode active material layer is 100 mg / 25 cm 2Up to 600 mg / 25 cm 2 Specifically, the loading amount per unit volume of the positive electrode active material layer may be 270 mg / 25 cm 2 Up to 800 mg / 25 cm 2 , 285 mg / 25 cm 2 Up to 700 mg / 25 cm 2 , or 300 mg / 25 cm 2 Up to 600mg / 25 cm 2 , and the loading amount per unit volume of the negative electrode active material layer may be 120 mg / 25 cm 2 Up to 500mg / 25 cm 2 、135 mg / 25 cm 2 Up to 400 mg / 25 cm 2 , or 150 mg / 25 cm 2 Up to 300 mg / 25 cm².

[0166] In addition to using the above-mentioned positive electrode active material and negative electrode active material, the positive electrode and the negative electrode can be manufactured by a typical method for manufacturing positive and negative electrodes. Specifically, the positive electrode and the negative electrode can be manufactured by drying and rolling the current collector after applying the active material layer forming composition (the composition contains the above-mentioned active material and optional binder and the conductive material) to the current collector. In this case, the type and content of the positive electrode active material and the negative electrode active material, the binder and the conductive material are as described above. The solvent can be a commonly used solvent in the art, examples of which include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc., and any one thereof or a mixture of two or more thereof can be used. Considering the coating thickness and manufacturing yield of the slurry, as long as the amount of the solvent used dissolves or disperses the active material, the conductive material, and the binder, and then has a viscosity that can show excellent thickness uniformity when used to manufacture the positive and negative electrodes. The amount of the solvent used is sufficient. Alternatively, as another method, the positive electrode and the negative electrode may be manufactured by casting the active material layer-forming composition on a separate support and then laminating a film obtained by peeling off the support on a current collector.

[0167] The diaphragm separates the negative electrode and the positive electrode, and provides a channel for lithium ion movement, and can be used without particular restriction, as long as the diaphragm is generally used as a diaphragm in a secondary battery, and in particular, it is preferred to have excellent electrolyte moisture retention ability and a diaphragm with low resistance to ion movement in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by a polyolefin-based polymer (such as, ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer) or a double-layer or more laminated structure thereof. In addition, a typical porous non-woven fabric can also be used, for example, a non-woven fabric made of glass fiber, polyethylene terephthalate fiber, etc. with a high melting point. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0168] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which may be used to prepare lithium secondary batteries, but are not limited thereto.

[0169] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0170] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.

[0171] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate as cyclic carbonates can be preferably used, because the cyclic carbonates have a high dielectric constant as a high-viscosity organic solvent, and therefore can dissociate lithium salts well. When the cyclic carbonates are mixed with low-viscosity and low-dielectric-constant linear carbonates (such as dimethyl carbonate and diethyl carbonate) in an appropriate proportion, an electrolyte with high conductivity can be prepared, so such a combined use is more preferred.

[0172] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, a metal salt selected from the group consisting of F - , Cl- ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - One or more of the groups consisting of.

[0173] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, one or more additives may be included, for example, halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0174] The lithium secondary battery according to an exemplary embodiment of the present invention may have an energy density of 400 Wh / L to 900Wh / L. Specifically, the lithium secondary battery may have an energy density of 425 Wh / L to 875 Wh / L, 450 Wh / L to 850Wh / L, 475 Wh / L to 825 Wh / L, or 500 Wh / L to 800 Wh / L. When the above range is met, the energy density of the lithium secondary battery designed in a limited space can be increased, its high output performance can be improved, and the battery cycle performance can also be improved.

[0175] A lithium secondary battery according to an exemplary embodiment of the present invention may be a cylindrical battery. A cylindrical battery means that the form of the battery itself is cylindrical, the battery includes an assembly including a positive electrode, a negative electrode, a separator, and an electrolyte, and specifically, the cylindrical battery may be composed of a cylindrical can, a battery assembly disposed in the cylindrical can, and a top cover. However, the lithium secondary battery is not limited thereto, and may be a square battery or a pouch-type battery.

[0176] An exemplary embodiment of the present invention provides a battery module including the cylindrical battery as a unit cell and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics and cycle characteristics, and can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.

[0177] Since the lithium secondary battery according to an exemplary embodiment of the present invention stably exhibits excellent discharge capacity, output characteristics and cycle performance, the lithium secondary battery can be used as a power source for portable devices (such as mobile phones, notebook-sized computers and digital cameras), and medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems. For example, the battery module or battery pack can be used as a power source for power tools; electric vehicles including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs); and one or more medium and large devices in power storage systems.

[0178] [Mode of invention]

[0179] Hereinafter, preferred embodiments will be presented to facilitate understanding of the present invention, but the embodiments are provided only for illustrating the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present invention, and such changes and modifications naturally also fall within the appended claims.

[0180] <Examples and Comparative Examples>

[0181] Example 1

[0182] (1) Preparation of negative electrode

[0183] A composition for forming a negative electrode active material layer is manufactured, based on 100 parts by weight of the negative electrode active material layer, the composition includes graphite as a negative electrode active material (containing artificial graphite and natural graphite in a weight ratio of 70:30, and based on 100 parts by weight of the negative electrode active material, its presence amount is 90 parts by weight) and silicon carbon composite (based on 100 parts by weight of the negative electrode active material, 10 parts by weight) 97.7 parts by weight, styrene butadiene rubber (SBR) 1.15 parts by weight and carboxymethyl cellulose (CMC) 1 part by weight as a binder, and also includes a CNT pre-dispersion, the CNT pre-dispersion includes 0.09 parts by weight of a dispersant and 0.06 parts by weight of single-walled CNT. A copper foil with a thickness of 15 μm is coated with the composition for forming a negative electrode active material layer so that it has a thickness of 86 μm in a dry state, and then dried to manufacture a negative electrode.

[0184] In this case, as the graphite, a graphite having a tap density of 1.1 g / cc and a D 50 Graphite, and as the silicon-carbon composite, a graphite having a tap density of 0.65 g / cc and a D of 5.1 μm was used. 50 Silicon carbon composite.

[0185] (2) Manufacturing of positive electrode

[0186] A positive electrode active material layer-forming composition was prepared, which contained 93.3 mol % Ni, 4.9 mol % Co and 1.8 mol % Mn as a positive electrode active material, and 98.04 parts by weight of a lithium composite transition metal compound containing single particles and secondary particles (single particles: secondary particles = 80:20 weight ratio), 1 part by weight of PVDF as a binder, and a CNT pre-dispersion containing 0.8 parts by weight of CNT as the conductive material and 0.16 parts by weight of a dispersant, based on 100 parts by weight of the positive electrode active material layer. A 30 μm thick aluminum foil was coated with the positive electrode active material layer-forming composition so that it had a thickness of 103 μm in a dry state, and then dried to manufacture a positive electrode.

[0187] In this case, as the single particle of the lithium composite transition metal compound, a lithium composite transition metal compound having a tap density of 1.8 g / cc and a diameter of 3.47 μm was used. 50 As the secondary particles of the lithium composite transition metal compound, a material having a tap density of 2.4 g / cc and a D of 9.5 μm was used. 50 materials.

[0188] (3) Manufacturing of lithium secondary batteries

[0189] The positive electrode and the negative electrode were stacked with a separator therebetween, and an electrolyte (1.0 M LiPF6, ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 30 / 70 (volume %), vinylene carbonate (VC) 1.5%) was injected to manufacture a lithium secondary battery.

[0190] Examples 2 to 4

[0191] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the positive electrode active material and the negative electrode active material having the tap density and particle size values ​​described in Table 1 below were used.

[0192] Comparative Examples 1 to 6

[0193] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the positive electrode active material and the negative electrode active material having the tap density and particle size values ​​described in Table 1 below were used.

[0194] The compositions of the negative electrode active materials prepared in Examples and Comparative Examples are shown in Table 1 below.

[0195]

[0196] The tap density of the positive electrode active material and the negative electrode active material is calculated by putting 40 g of a sample in a container and tapping the container 1000 times using a TAP-2S apparatus manufactured by LOGAN Corporation.

[0197] The positive electrode active material and the negative electrode active material each have 50 Analyzed by PSD measurement method using a Microtrac device.

[0198] The porosity of the active material layers of the positive electrode and the negative electrode was calculated using the following relationship.

[0199] Porosity of electrode active material layer (%) = {1-(density of active material layer / true density of active material layer)} x 100

[0200] The aspect ratio, true density, and BET specific surface area of ​​the graphite and the silicon-carbon composite of the negative electrode active materials prepared in Examples and Comparative Examples are shown in Table 2 below.

[0201] In the following, the true density of the active material layer is obtained by pressing a 3*4 (cm 2 ) is pressed until the thickness of the negative electrode does not change and the density of the active material layer of the electrode is measured, and the density of the active material layer is the density of the active material layer measured by sampling the electrode with the same size before pressing.

[0202]

[0203] <Experimental Example: Evaluation of Discharge Capacity, Initial Efficiency, and Lifespan (Capacity Retention Rate) Characteristics>

[0204] The discharge capacity, initial efficiency, and capacity retention ratio were evaluated by charging and discharging the lithium secondary batteries manufactured in Examples and Comparative Examples, and are shown in Table 3 below.

[0205] For the 1st and 2nd cycles, the battery was charged and discharged at 0.1 C, and from the 3rd cycle to the 49th cycle, the battery was charged and discharged at 0.5 C. The 50th cycle was completed in a charged state (in which lithium was contained in the negative electrode).

[0206] Charging conditions: CC (constant current) / CV (constant voltage) (5 mV / 0.005 C current cutoff)

[0207] Discharge condition: CC (constant current) condition 1.5 V

[0208] The discharge capacity (mAh / g) and initial efficiency (%) were obtained from the results during the first charge and discharge. Specifically, the initial efficiency (%) was obtained by the following calculation.

[0209] Initial efficiency (%) = (first discharge capacity / first charge capacity) × 100

[0210] The capacity retention ratios were each calculated as follows.

[0211] Capacity retention rate (%) = (49th discharge capacity / 1st discharge capacity) × 100

[0212] <Experimental Example: Evaluation of Electrode Thickness>

[0213] The thickness of the positive electrode and negative electrode manufactured in the embodiment and the comparative example was measured respectively using a Micro-Hite 350 (Tesa) device, and then summed. The average value of about three measurements was taken and calculated as the thickness of the electrode. The calculated electrode thickness in Example 1 was set to 100%, and the electrode thickness in Examples 2 to 4 and Comparative Examples 1 to 6 was relatively calculated based on the calculated thickness, and is shown in Table 3 below.

[0214] <Experimental Example: Evaluation of Li plating time point>

[0215] The first and second cycles were charged and discharged at 0.1 C, and from the third cycle onwards the battery was charged and discharged at a rate of 3 C, and the resistance of the battery was measured.

[0216] Charging conditions: CC (constant current) / CV (constant voltage) (5 mV / 0.005 C current cutoff)

[0217] Discharge conditions: CC (constant current) condition 1.5V

[0218] The point at which the battery resistance suddenly drops and the current value suddenly changes is calculated as the time point at which Li deposition occurs.

[0219]

[0220] According to Tables 1 to 3 above, it can be confirmed that, when compared with Comparative Examples 1 to 6, the secondary batteries of Examples 1 to 4 using the negative electrode in which the tap density of graphite is equal to or greater than the tap density of the silicon-carbon composite have a smaller electrode thickness and show a better capacity retention rate, and the charging capacity, etc. are significantly improved by observing that the lithium precipitation time point of lithium precipitation is SOC 95% or more. This seems to be because the tap density of graphite is equal to or greater than the tap density of the silicon-carbon composite, so that the graphite can be densely dispersed throughout the electrode, which makes the current flow in the negative electrode uninterrupted and makes it easier to adjust the orientation of the graphite in the negative electrode. In contrast, in the case of Comparative Examples 1 to 6, since the tap density of the graphite is less than the tap density of the silicon-carbon composite, the graphite aggregates rather than disperses in the electrode, and therefore, due to the poor dispersibility of the slurry, it is unfavorable in rolling, so that it can be confirmed that the electrode thickness is significantly increased, the capacity retention rate is also reduced, and the charging capacity, etc. are deteriorated at the lithium precipitation time point SOC of 82% to 90%.

Claims

1. A negative electrode composition comprising a negative electrode active material, wherein the negative electrode active material comprises a silicon-carbon composite and graphite, The tap density of the graphite is equal to or greater than the tap density of the silicon-carbon composite. 2 . The negative electrode composition according to claim 1 , wherein the graphite has a tap density of 0.9 g / cc to 1.2 g / cc. 3 . The negative electrode composition according to claim 1 , wherein the silicon-carbon composite has a tap density of 0.5 g / cc to 1.15 g / cc. 4 . The negative electrode composition according to claim 1 , wherein the silicon-carbon composite has an average particle size of 1 μm or more and 15 μm or less. 5 . The negative electrode composition according to claim 1 , wherein an average particle size of the silicon-carbon composite is smaller than an average particle size of the graphite. 6 . The negative electrode composition according to claim 1 , wherein the graphite has an aspect ratio of 0.8 to 0.9, and the silicon-carbon composite has an aspect ratio of 0.3 to 0.

7. 7 . The negative electrode composition according to claim 1 , wherein the graphite has a true density of 2 to 3 g / cc, and the silicon-carbon composite has a true density of 1.8 to 2.2 g / cc.

8. The negative electrode composition according to claim 1, wherein the graphite has a m 2 / g, and the silicon-carbon composite has a BET specific surface area of ​​1 to 10 m 2 / g BET specific surface area. 9 . A negative electrode, comprising: a negative electrode current collector; and a negative electrode active material layer, the negative electrode active material layer being provided on one or both surfaces of the negative electrode current collector layer and comprising the negative electrode composition according to claim 1 . 10 . The negative electrode according to claim 9 , wherein the negative electrode active material layer has a porosity of 23% to 28%. 11 . A lithium secondary battery comprising: a positive electrode; the negative electrode according to claim 9 ; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

12. The lithium secondary battery according to claim 11, wherein the positive electrode comprises a lithium composite transition metal compound as a positive electrode active material, the lithium composite transition metal compound comprising nickel (Ni), cobalt (Co) and manganese (Mn), and the lithium composite transition metal compound comprises a single particle. 13 . The lithium secondary battery according to claim 12 , wherein the lithium composite transition metal compound further comprises secondary particles. 14 . The lithium secondary battery according to claim 13 , wherein the tap density of the secondary particles is greater than the tap density of the single particle. 15 . The lithium secondary battery according to claim 12 , wherein the tap density of the single particle is greater than the tap density of the graphite. 16 . The lithium secondary battery according to claim 12 , wherein the single particle has an average particle diameter of 1 μm or more and 12 μm or less. 17 . The lithium secondary battery according to claim 12 , wherein an average particle size of the single particles is smaller than an average particle size of the silicon-carbon composite.

18. The lithium secondary battery according to claim 12, wherein the content of the single particle is 15 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material, and The silicon-carbon composite may be present in an amount of 3 to 30 parts by weight relative to 100 parts by weight of the negative electrode active material. 19 . The lithium secondary battery according to claim 12 , wherein the lithium composite transition metal compound contains 80 mol % or more of nickel in metals other than lithium. 20 . A battery module comprising the lithium secondary battery according to claim 11 .

21. A battery pack comprising the battery module according to claim 20.

Citation Information

Patent Citations

  • Negative electrode material for nonaqueous electrolytic secondary battery, process for producing negative electrode material for nonaqueous electrolytic secondary battery, and lithium ion secondary battery

    KR1020110112215A